Implementation of APAPO from Technology Acceptance Model and Sosial Affordances - Elyan Nadian Zahara (Jurnal Ilmiah Kajian Keimigrasian, 2020)
The purpose of this study is to explain how was the Implementation of Online Passport Queue Registration Application (APAPO) based on TAM and social affordances. This study is a conceptual paper using qualitative approach with literature review. APAPO is used as a unit of analysis with Directorate General of Immigration’s public complaint data as a purposive sample. From the result, it was recognized that APAPO was not well-received by users and had low social affordances.